Analisis penguatan karakter religius siswa kelas III melalui budaya sekolah di SD Muhammadiyah 2 Gempol - Yenny Anugerah Zafirah Auliyah; Muhlasin Amrulloh; Khizanatul Hikmah (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
This study aims to find out and describe the application of strengthening the religious character of third grade students through school culture along with the supporting factors and inhibiting factors in efforts to strengthen religious character carried out at Muhammadiyah 2 Gempol Elementary School. This research is a qualitative research using a phenomenological approach. Sources of data in this study are school principals, teachers, and third grade students. Data analysis techniques in this study are data collection, data reduction, data presentation, and drawing conclusions. The validity of the data in this study used two types of triangulation, namely source triangulation and technical triangulation. The results of this study indicate that the application of strengthening the religious character of grade III students through school culture is carried out through several activities, such as prayer activities before and after learning, Dhuhur and Dhuha prayers in congregation, morning habituation activities, 6S habituation, Al-Quran tahfidz activities, infaq every Friday, adiwiyata, Friday blessing, and activities on religious days. The supporting factors for the success of strengthening the religious character of grade III students come from adequate facilities and infrastructure, exemplary forms from teachers, and cooperation between teachers, parents, and students. As for the inhibiting factors for success such as the different abilities of students, as well as the demands for grades from the general field of study.